Chinese soft power : case study of climate cooperation with the EU - Dosdá, Renata; Dubský, Zbyněk, 1974-; Kočí, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
China, as an emerging power, faces pressure to take on more responsibility for global climate change. Its leadership has adapted to this, recognizing the importance of addressing climate impacts. Worldwide emissions reduction has become a global goal. This thesis examines whether China's investments in renewable energy in Europe and its proactive environmental policies contribute to its soft power strategy. The research investigates China's environmental diplomacy with the EU using Joseph Nye's concept of soft power. It analyzes soft power resources, and Chinese investments in eco-friendly projects like the BRI, and evaluates official statements and discourse since 2004, including climate negotiations from 2009 to 2018. This approach combines primary and secondary sources for a comprehensive perspective. Through qualitative case study analysis, it finds that China is leveraging soft power to build a positive national image as a climate change leader, actively engaging in climate negotiations and environmental diplomacy through soft power instruments such as signaling and strategic narratives.
Vedoucí práce: Zbyněk Dubský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor dipl. práce]; diplomové práce; master's theses